(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides an in-depth analysis of the historical, terminological, and practical significance of the Latin language as a means of interstate communication in medicine. It highlights the universal role of Latin in anatomical, clinical, and pharmacological terminology, its place in international scientific cooperation, communication during pandemics, telemedicine, and digital health systems. The strategic importance of Latin’s neutrality, precision, and provision of global medical standards is demonstrated, and the relevance of its preservation and development in modern medicine is substantiated.